Perspectives and challenges of student affairs graduate assistants in residence life: understanding experiences to enhance professional practice - Brown, Naima M. (Kansas State University, 2013)
Graduate assistants in residence life face many different challenges that are unique to their positions, and their wellness is critical to ensuring their place as competent professionals ready to serve students on university campuses. For the continued success and relevance of graduate assistantship positions in housing departments, it is critical that an effort be made to understand these student employees’ experiences as they complete graduate study and are employed under various expectations that may be directly impactful to the manner in which they work with students. This report serves to understand the experiences of residence life graduate assistants to better prepare full-time professionals in supervising and supporting these individuals.
Keywords: Graduate assistant; Student affairs; Residence life; Higher Education (0745)